The lower boundary of workplace mistreatment: Do small slights matter? - Michal Hodor; Liat Eldor; Peter Cappelli (Proceedings of the National Academy of Sciences, 2025)
Recent research in psychology, management, and more recently in economics, highlights the role of individual managers and their behavior in shaping employee performance. While emerging literature on harmful managerial behavior has focused primarily on severe forms of workplace mistreatment, especially various types of harassment, much less is known about its boundary conditions: How minor can a manager’s bad behavior be and still negatively affect employee performance? We study what appears to be a very minor workplace mistreatment—failing to deliver an expected birthday gift and greeting card on time—and examine its effect on subsequent employee performance. Using a dynamic difference-in-differences approach with detailed data from a national retail chain, we find that this small slight leads to over a 50% increase in employee absenteeism and a reduction of more than two working hours per month. Our analysis suggests that emotional responses to perceived workplace mistreatment drive the results. These findings indicate that even modest slights can meaningfully harm employee performance.